The talent code : greatness isn't born. It's grown. Here's how. - Coyle, Daniel (New York : Bantam Books, 2009)
This book shows you how to grow talent by tapping into a newly discovered brain mechanism. Drawing on cutting-edge neurology and firsthand research gathered on journeys to nine of the world's talent hotbeds, author Coyle identifies the three key elements that will allow you to develop your gifts and optimize your performance in sports, art, music, math, or just about anything.--From publisher description.
Includes bibliographical references (p. [223]-232) and index.
Keywords: Ability; Motivation (Psychology)